Hydroalcoholic extract of leaves of Arrabidaea brachypoda (DC.) Bureau present antispasmodic activity mediated through calcium influx blockage - Fabio de Souza Monteiro; Jhone Robson da Silva Costa; Lenivaldo Jorge Alves Martins; Cláudia Quintino da Rocha; Antonio Carlos Romao Borges; Marilene Oliveira da Rocha Borges (São Paulo State University (UNESP), 2020)
Aim: Since other species of the Bignoniaceae Family presented of antispasmodic activity, it was decided, by chemotaxonomic criterion, to determine the antispasmodic activity of the leaves of Arrabidaea brachypoda. Methodology: the segments of the rat jejunum were suspended in glass vats containing specific saline solution, at an appropriate temperature, and after stabilization period, were stimulated by a contractile agent to observe the inhibitory or relaxing effect of EHFAB. Results: EH-FAB showed the presence of 10 compounds, mainly rutin and it has an antispasmodic activity as it inhibits the phasic component and relaxes the tonic component of the contraction in isolated rat jejunum. To assess the mechanism of antispasmodic action, cumulative curves to the CCh were performed in which a non-competitive antagonism was observed, due to a displacement of the control curve to the right and reduction of the maximum contraction effect (Emax). Afterward, the participation of the calcium and/or potassium channels was evaluated by increasing the extracellular potassium, and it was observed that the EH-FAB relaxed the rat jejunum, suggesting the participation of the Ca2+ channels. To corroborate that hypothesis, the EH-FAB was tested against cumulative curves to Ca2+ in a free depolarizing solution of Ca2+, and it was observed that there was a shift of the curve to the right with a reduction in Emax. Conclusions: EH-FAB presents antispasmodic activity in isolated rat jejunum and it is suggested to block the influx of Ca2+ through voltage-gated calcium channels, signaling the therapeutic potential for the treatment of colic and/or diarrhea.